Effective liquid-phase photocatalytic reaction using a newly developed titanium oxide-assisted reactor with ozone microbubble treatment - Kim, Kyung Hwan; Sekiguchi, Kazuhiko; Yoshida, Takeshi; Yasui, Fumio; Tamura, Hajime (ELSEVIER SCIENCE BV, 2014)
We have developed a TiO2-assisted reactor that improved the UV light penetration into the solution during the photocatalytic decomposition of isopropyl alcohol (IPA). Increasing the UV penetration enhanced the decrease in the concentration of acetone, which is the main IPA decomposition product, and the total organic carbon. However, it did not affect the decrease in IPA concentration. Charging the solution with O-3 microbubbles significantly increased mineralization for the first 5 h of the reaction. Our results can be used to improve the efficiency of UV sources and develop an ecologically friendly, practical wastewater treatment for IPA. (C) 2014 Elsevier B.V. All rights reserved.